2020
DOI: 10.1186/s41938-020-00241-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial insect community of Moroccan citrus groves: assessment of their potential to enhance biocontrol services

Abstract: In citrus groves, beneficial insects that reduce abundance of pests are considered a key component of integrated pest management strategies. The aim of this article was to assess the biodiversity of parasitoids and predators in citrus orchards in Moroccoto facilitate future investigations on their potential as biocontrol agents. Data of 105 citrus beneficial insects were gathered and summarized in a data matrix. Variables such nature, target pests, type, establishment, and efficacy were assessed. More than two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A study conducted in Italy showed that the simultaneous release of beneficial phytoseiid mites, Amblyseius aberrans and Typhlodromus pyri, in a vineyard infested by Panonychus ulmi provided significant control [43]. In Morocco, the new introduction in citrus orchards of the predators Neoseiulus californicus McGregor (Acari: Phytoseiidae) and Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) against the oriental mite Eutetranychus orientalis and T. urticae ensures good results [5]. Similarly, in Spain, the control of T. urticae through releases of the predatory mites P. persimilis, N. californicus, A. swirskii Athias-Henriot, 1962, and Orius laevigatus Fieber, 1860, (Hemiptera: Anthocoridae) showed significant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Italy showed that the simultaneous release of beneficial phytoseiid mites, Amblyseius aberrans and Typhlodromus pyri, in a vineyard infested by Panonychus ulmi provided significant control [43]. In Morocco, the new introduction in citrus orchards of the predators Neoseiulus californicus McGregor (Acari: Phytoseiidae) and Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) against the oriental mite Eutetranychus orientalis and T. urticae ensures good results [5]. Similarly, in Spain, the control of T. urticae through releases of the predatory mites P. persimilis, N. californicus, A. swirskii Athias-Henriot, 1962, and Orius laevigatus Fieber, 1860, (Hemiptera: Anthocoridae) showed significant results.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, exports to Russia have increased from 45% to 50% of all Moroccan exports [4]. Unfortunately, this sector has been seriously affected in recent years by biotic and abiotic factors [5]. In addition to production and marketing complications, many pests and diseases have reduced the quantity and quality of citrus fruit [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, the releasing of predators Chrysoperla carnea (Steph, 1836), Orius albidipennis (Reuter, 1884), and P. persimilis showed significant control of T. urticae, and it also assured increased crop yield as compared to pesticide application [110]. In Morocco, the new introduction in citrus orchards, such as the predators Neoseiulus californicus and Amblyseius swirskii against Eutetranychus orientalis (Klein, 1936) and T. urticae have produced good results [111]. Similarly, in Spain, the control of T. urticae through releases of the predatory mites Phytoseiulus persimilis, Neoseiulus californicus, Amblyseius swirskii, and Orius laevigatus Fieber, 1860 (Hemiptera: Anthocoridae) showed significant results.…”
Section: Combined Releasesmentioning
confidence: 99%
“…Euseius stipulatus Athias-Henriot, 1960 (Acari: Phytoseiidae), Phytoseiulus persimilis Athias-Henriot, 1957 (Acari: Phytoseiidae), and Typhlodromus sp. (Acari: Phytoseiidae) are the main predators of T. urticae in many regions of the world [ 16 , 17 ]. Spirodiclofen (Envidor 240 SC, Bayer, SA) is an acaricide of the keto-enol family.…”
Section: Introductionmentioning
confidence: 99%